Liquid exfoliation of alkyl-ether functionalised layered metal–organic frameworks to nanosheets. Issue 69 (25th July 2016) - Foster, Jonathan A.; Henke, Sebastian; Schneemann, Andreas; Fischer, Roland A.; Cheetham, Anthony K.
Abstract : Dispersion of the nanosheets exposes labile metal-sites which are shown to exchange solvent molecules allowing the nanosheets to act as sensors in suspension. Abstract : We report the synthesis of a 2D-layered metal–organic framework incorporating weakly interacting chains designed to aid exfoliation of the layers into nanosheets. Dispersion of the nanosheets exposes labile metal-sites which are shown to exchange solvent molecules allowing the nanosheets to act as sensors in suspension.